Fluidised-MCPCM glazed energy storage system - Thaicham, Pruitipong. (2004)
The thesis presents an experimental investigation into the feasibility of using a slurry containing a micro encapsulated phase change material (MCPCM), n-eicosane, as a heat transfer fluid for enhanced latent heat transport. Increasing the convective heat transfer coefficient would permit the use of a smaller volumetric flow rate and reduce pumping power. The primary parameters investigated are the volumetric concentrations and flow rates. Measurements of thermal capacity of the novel slurries were performed using two techniques, standard differential scanning calorimeter (DSC) and thermal analysis (TA). Pumping power consumption, viscosity and pressure loss of the flowing slurries were investigated in order to determine the most suitable concentration of MCPCM used in the slurry, over the range 5-40%. The effects of repeated use of liquid-solid phase change particles upon melting and solidifying were studied using a small-scale rig of a closed loop circuit. The research work further involved the design, construction and tests the proposed system based on incorporating microencapsulated phase change material (MCPCM) within a fluidised and sealed double glazed panel, which could be integrated into building fabric.